Heart and Head - Hopkins, D. author. aut Link
XIV, 222 p.
Keywords: Faith, hope, and love embody the black theology of liberation, a movement created by a group of African- American pastors in the 1960s who felt that Christ's gospel held a special message of liberation for African- Americans, and for all oppressed people. Beginning with an intimate introduction, Hopkins writes of his mother's death, when he was nine, and reveals that his father's love for the poor influenced him to become a Minister and to pursue a life of service which required 'a compassionate intellect and an intellectual compassion. Hopkins asserts that in this post-Civil Rights, post-affirmative action era, that all people, regardless of race, must join together in forging a new common wealth. Offering a detailed perspective on a new racial, gender, and economic democracy in the United States, Hopkins illustrates that black theology can be the key to personal and global liberation.